Dynamics of Normalization in the New Middle East: An Analysis of the Abraham Accords and Arab Strategic Interests - Burdah, Ibnu (Jurnal Review Politik, 2024)
In January 2020, President Donald Trump introduced the Abraham Accords, often hailed as the deal of the century. Many criticized the proposal for focusing solely on U.S. diplomatic peace efforts in the Middle East and shifting the core issue from the Israeli-Palestinian conflict to the normalization of Arab-Israeli relations. Despite its controversies, the Abraham Accords normalized relations between Israel and the United Arab Emirates and Bahrain, potentially reshaping the "New Middle East" differently. This article explains the Abraham Accords, which primarily involve several Arab countries recognizing Israel's sovereignty and their willingness to establish full diplomatic relations with the Jewish state. The researcher draws two key conclusions by reviewing the process, content, atmosphere, and responses to the agreement. First, although the agreement seemed sudden, its achievement involved a complex, lengthy, and not entirely planned process. Second, Arab countries pursued this option not only out of solidarity with Palestine or pressure from their patron, the United States, but also to achieve various strategic interests—political, military, economic, and others—thereby effectively sidelining the Pales ti nian issue.